PREPARATION AND CHARACTERIZATION OF POLYOL NATURAL RUBBER LATEX BASED POLYURETHANE FOAM - Fransiskus Gultom (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this study was to preparate and characterize polyurethane foam by using a polyol natural rubber latex. Polyurethane synthesized from polypropylene glycol (PPG), Toluene Diisocyanates (TDI) and polyols Natural Rubber Latex. Polyurethane foam that is formed then characterized by mechanical properties and morphology using Scanning Electron Microscopy (SEM). Mechanical properties and morphology of the polyurethane foam is the optimum addition of 50% polyol natural rubber latex in the manufacture of polyurethane foam.Keywords: toluene diisocyanates, polypropylene glycol, polyols, natural rubber latex